Whether coconut water can be used or not as an alternative of radiographic contrast media? a preliminary study - Norasip, Nurul Nadiah; Sayed, Inayatullah Shah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Radiographic contrast medium is primarily used to enhance the contrast of the internal structure in diagnostic imaging. However, the adverse reactions of administration of contrast media have become a great concern and challenge since it can affect the life of patient. Even though some safety measurements have been highlighted by several studies, still, the occurrence of adverse effects of contrast media is one of the issues in medical imaging. There are several similar properties between the young coconut water and contrast media used in radiography. Thus, the objective of this research was to investigate whether the young coconut water be used as an alternative to contrast media. Polyvinyl chloride tubes with equal internal diameter labeled A and B were inserted into a small tunnel of contiguous slices of Art Phantom. In the tube A contrast medium of Omnipaque 350 mgI/ml and in B tube young coconut water was filled. The phantom was exposed using general x-ray system Siemens MULTIX Top with two different parameter settings, i.e., 73 kVp @ 1.89 mAs and 81 kVp @ 1.85 mAs. Image quality criteria scoring were performed to evaluate the image quality of radiographs. Results showed no improvement and poor detectability of tube B in the radiograph with the coconut water as compared to contrast medium. In conclusion, the coconut water specifically used in this study could not be used as an alternative to contrast media. However, more research could be conducted with the use of similar viscosity of the coconut water as contrast media as an alternative contrast agent.